Recurrent eccrine hidradenoma of the breast in a male patient: problems in differential diagnosis - Maria Orsaria; Laura Mariuzzi (Our Dermatology Online, 2013)
Introduction: Hidradenoma is an uncommon usually benign tumor of the skin that grows slowly.Case presentation: We describe a case of a 39 patient with a breast mass. Physical examination revealed a solitary, well-circumscribed tumor, measuring 1 cm by 0.7 cm. No other skin abnormalities were found. A total surgical excision was performed and histologic examination concluded to an eccrine hidradenoma with clear cells.Conclusion: Here we discuss problems in the differentiate this tumor, mainly in this not common location, from a breast primary (ductal carcinoma or adenomyoepitelioma), from a metastatic clear cell carcinoma and from other types of skin tumors. Moreover, this patient presented with a recurrence of the tumor in the same location, suggesting a locally aggressive form of this neoplasia; few reports in the literature are described as at low malignant potential, but definite criteria for this diagnosis are not well defined.